Maintenance fundamentals - Mobley, R. Keith, 1943- (Elsevier/Butterworth Heinemann, 2004)
No matter which industry a company is a part of, its profitability, like its products, is driven by the reliability and performance of its plant(s). The fundamentals for maintenance found in this volume are applicable to a multitude of industries: power, process, materials, manufacturing, transportation, communication, and many others. This book shows the engineer how to select, install, maintain, and troubleshoot critical plant machinery, equipment, and systems. NEW to this edition: New material includes a chapter on inspections, providing practical guidelines for effective visual inspections, the key to effective preventive maintenance. Also included in the revision will be multiple chapters on equipment, such as pumps, compressors, and fans. *Provides practical knowledge about plant machinery, equipment, and systems for the new hire or the veteran engineer *Covers a wide array of topics, from shaft alignment and bearings to rotor balancing and flexible intermediate drives *Delivers must-have information to the engineer which he/she will use on a daily basis, in day-to-day activities, that will affect the reliability and profitability of the plant.